2013
DOI: 10.1242/jcs.123547
|View full text |Cite
|
Sign up to set email alerts
|

Spatial regulation of RhoC activity defines protrusion formation in migrating cells

Abstract: SummaryProtrusion formation is the first step that precedes cell movement of motile cells. Spatial control of actin polymerization is necessary to achieve directional protrusion during cell migration. Here we show that the spatial coordinators p190RhoGEF and p190RhoGAP regulate actin polymerization during leading edge protrusions by regulating the actin barbed end distribution and amplitude. The distribution of RhoC activity and proper balance of cofilin activation achieved by p190RhoGEF and p190RhoGAP determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
70
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 62 publications
(94 reference statements)
3
70
0
Order By: Relevance
“…In tumor cells it was also shown that in the absence of a lamellipodium, RhoA displayed high activation levels in mDia1-dependent finger like protrusions that formed after EGF stimulation. 49 Furthermore, biosensor technology has shown how RhoA activity is regulated in other cellular processes such as cytokinesis 50 and T-cell transendothelial migration. 51 The RhoA biosensor design has evolved since the first version 44,45 ( Fig.…”
Section: The Abcs Of Rho Gtpasesmentioning
confidence: 99%
See 4 more Smart Citations
“…In tumor cells it was also shown that in the absence of a lamellipodium, RhoA displayed high activation levels in mDia1-dependent finger like protrusions that formed after EGF stimulation. 49 Furthermore, biosensor technology has shown how RhoA activity is regulated in other cellular processes such as cytokinesis 50 and T-cell transendothelial migration. 51 The RhoA biosensor design has evolved since the first version 44,45 ( Fig.…”
Section: The Abcs Of Rho Gtpasesmentioning
confidence: 99%
“…57 The RhoC biosensor was used to reveal the mechanism by which RhoC contributes to the invasion of tumor cells. Spatial activation of RhoC surrounding the core of invasive protrusions named invadopodia 56 or within regions located behind the leading edge 49 triggers a signaling pathway that phosphorylates cofilin 58 and confines cofilin activity and actin polymerization at the core of invadopodia or to the tip of the leading edge, a localization which is essential for efficient invasion. These activation zones are regulated by the spatial and geometric arrangements of the direct upstream regulators p190RhoGEF and p190RhoGAP.…”
Section: The Abcs Of Rho Gtpasesmentioning
confidence: 99%
See 3 more Smart Citations